Exploring farmer’s assessment of soil quality and root yield in cassava-based cropping systems - Mesele, S.A.; Soremi, P.S.; Adigun, J.K. (2024)
Farmers’ knowledge of soil quality and yield assessment were evaluated among cassava farmers in southwestern Nigeria. Data were collected on farmers’ demography, farming experience, criteria for selecting a site for cassava cultivation and preferences for those criteria, farmers’ methods of yield prediction and how it compares with the scientific approach, farmers’ agronomic knowledge and how it relates to the realities of climate change and soil fertility decline. The modal age class of the farmers is 45–55 years, and most of the farmers are male. The results show that farmers use a combination of soil and vegetation-based criteria to assess soil quality from which the decision to cultivate a given land is made. Among the soil-based criteria, soil drainage, colour, and depth rank the most and most used. Most of the farmers assessed yield before harvesting through green healthy leaves (25 %), large and shiny stems (25 %) and soil cracks (50 %). The predicted and measured cassava yields on farmer-managed farms were comparable, with an R2 of 0.63, although farmers overestimated the cassava root yield. There is a unanimous consensus among farmers that yield has declined in the last decade, with a mean of 36 %. The main cause of yield decline was attributed to declining rainfall and poor soils. Our study concluded that farmers have a good understanding of soil health and cassava agronomy through a process of trial and error and ingenuity as farmers’ local indices were consistent with conventional soil health indicators. It was suggested that, by recognising and incorporating traditional methods used by farmers to assess soil quality, we could enhance soil management strategies and raise productivity at the farm level.